2009
DOI: 10.1177/0890334409353748
|View full text |Cite
|
Sign up to set email alerts
|

Iron Concentrations in Breast Milk and Selected Maternal Factors of Human Milk Bank Donors

Abstract: The aim of this study was to evaluate the relationship between iron concentration in mature breast milk and characteristics of 136 donors of a Brazilian milk bank. Iron, vitamin A, zinc, and copper concentrations were assessed in human milk and maternal blood. Data were collected on maternal anthropometrics, obstetric, socioeconomic, demographic, and lifestyle factors. Iron, zinc, and copper in milk and zinc and copper in blood were detected by spectrophotometry. Vitamin A in milk and blood was determined by h… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
3
0
2

Year Published

2011
2011
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(6 citation statements)
references
References 27 publications
1
3
0
2
Order By: Relevance
“…Therefore, there is no clinical or scientifi c support for the need of extra iron to the newborn, in addition to amounts provided by breast milk of term lactating woman, at least during the fi rst six months. Regarding income, there was no signifi cant difference associated with the iron, this result was also observed among women in other research 35 . The others factors socioeconomic, demographic and lifestyle tested showed no signifi cant associations.…”
Section: Artigo Geralsupporting
confidence: 78%
“…Therefore, there is no clinical or scientifi c support for the need of extra iron to the newborn, in addition to amounts provided by breast milk of term lactating woman, at least during the fi rst six months. Regarding income, there was no signifi cant difference associated with the iron, this result was also observed among women in other research 35 . The others factors socioeconomic, demographic and lifestyle tested showed no signifi cant associations.…”
Section: Artigo Geralsupporting
confidence: 78%
“…There is no evidence that oral contraceptive use, infection, or β-thalassemia major affect iron concentrations in breast milk despite their role in altering iron metabolism (151). There is inconclusive evidence that breast milk iron concentrations are associated with parity (166), milk vitamin A concentrations, and smoking (167). A single study found higher iron concentrations in hindmilk and in samples collected during the night (166).…”
Section: Ironmentioning
confidence: 99%
“…21,22 Conversely, other studies have shown that maternal nutritional status affects human milk composition. 23,24 The variable age also did not show correlation with bacterial growth, and this was probably because an adult population (25.2 ± 6.6 years) was studied. It is known that human milk from teenager mothers has nutritional deficiencies due to their fast growth during this period.…”
Section: Discussionmentioning
confidence: 92%